(untitled) (Zaporizhzhia Historical Review, 2021)
Bronze cheek-pieces belonged to the one of largest groups of horse-gear elements in Eastern and Central Europe in the 9th -7th centuries BC. In recent years several classification of the pre-Scythian cheek-pieces from Central Europe, North Caucasus and Pontic steppe area were proposed by different archaeologists (U.Dietz, C.Metzner-Nebelsick, J.Chochorowski, S.Dudarev, V.Erlikh, S.Valchak). The article is devoted to the analysis of these conceptions as well as to elaboration of author’s own classification, which is suitable all existing materials in Eastern and Central Europe. It is based on the cheek-pieces constructional features and does not include their manufacture technology and decor.